Fast University Timetabling via Room-wise CP-SAT Decomposition and Incremental Repair - Moreira, Éber Júnio Borges; Freitas, Sérgio Antônio Andrade de (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
We propose a room-wise CP-SAT decomposition with incremental repair to speed up the course timetabling problem. We solve per-room subproblems and enforce cross-room instructor non-overlap via incremental global blocking. When infeasibility arises, we apply selective rollback and a controlled fallback that preserves completeness but can introduce instructor conflicts; all runs are checked by a global validator reporting coverage, violations, and perlecture preference satisfaction. On 11 real instances from a large Brazilian public university (DS1–DS11, up to 6,278 lectures), we achieved 100% coverage in all runs and solved the largest case in seconds (4.45 s on DS11), with high preference satisfaction when fallback was not triggered (89.6% on DS11).